EFEKTIVITAS PELAYANAN PUBLIK DALAM PROGRAM PEMBERIAN BANTUAN PANGAN NON TUNAI (BPNT) DI DESA GILANG KECAMATAN TAMAN KABUPATEN SIDOARJO - Kartika Santi Ratna Puspita; Susi Ratnawati; Fierda Nurany (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
Poverty is still an economic problem in Indonesia today. Based on the population's poor quality of life, poverty can be seen., limitations in meeting daily needs, low quality of health services, child nutrition, and education. The Non-Cash Food Assistance (BPNT) program is one of the measures used by the government to combat the issue of poverty. BPNT is one of the government's programs by providing basic food assistance to Beneficiary Families (KPM) in the amount of Rp 200,000/month through the Family Welfare Card (KKS) in electronic form called E-Warong. This study aims to measure the effectiveness of the BPNT program in Gilang Village, Taman District, Sidoarjo Regency. This research uses qualitative approach obtained through documentation and interview techniques. This research measures effectiveness including program understanding, on target, on time, goal achievement, and real change. According to research, the Non-Cash Food Assistance Program (BPNT) in Gilang Village, Taman District, Sidoarjo Regency can be said to be effective, However, there are still unfavorable indicators, such as the frequently delayed administration and the provision of assistance is still not on target.